2013
DOI: 10.1111/bjh.12292
|View full text |Cite
|
Sign up to set email alerts
|

The inferior prognosis of adolescents with acute lymphoblastic leukaemia (ALL) is caused by a higher rate of treatment‐related mortality and not an increased relapse rate – a population‐based analysis of 25 years of the Austrian ALL‐BFM (Berlin‐Frankfurt‐Münster) Study Group

Abstract: The inferior prognosis of adolescents with acute lymphoblastic leukaemia (ALL) is caused by a higher rate of treatment-related mortality and not an increased relapse rate -a population-based analysis of 25 years of the Austrian ALL-BFM (Berlin-Frankfurt-M € unster) Study Group SummaryAdolescents aged 15-18 years with acute lymphoblastic leukaemia (ALL) have been historically reported to have a poorer prognosis than younger children. We retrospectively analysed the characteristics and outcome of 67 adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…Previously published studies showed that, also in acute lymphoblastic leukemia, adolescents are more fragile than children. [25][26][27] The reasons behind the observation that adolescents have an increased risk for death in CCR are unclear, but they may reflect age-dependent differences in immunologic response to infections and tissue toxicity following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies showed that, also in acute lymphoblastic leukemia, adolescents are more fragile than children. [25][26][27] The reasons behind the observation that adolescents have an increased risk for death in CCR are unclear, but they may reflect age-dependent differences in immunologic response to infections and tissue toxicity following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the strategy using intensive pediatric chemotherapy while minimizing the indication of HSCT was feasible for adolescent patients with AML. Meanwhile, reports on AYA patients with ALL showed that adverse events such as severe infection, osteonecrosis, thrombosis, and hyperglycemia are generally more problematic in older patients, although the latter three events are associated with an intensive use of corticosteroids and/or asparaginase that are not commonly used in therapies for AML [11][12][13]26]. In fact, previous reports on AYA patients with AML from the St. Jude Children's Research Hospital and COG both showed significantly higher TRD compared to younger AML patients [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Young adult patients also experience a higher rate of treatment-related morbidity and mortality, particularly secondary to infection, osteonecrosis, and thrombosis. 30,31 Multiple studies have demonstrated the benefit of treating adolescent and young adult patients with ALL on pediatric-based protocols. 32 …”
Section: Considerations For Particular Subgroups Of Acute Lymphoblastmentioning
confidence: 99%